Tacrolimus therapy in moderate to subacute ulcerative proctocolitis: a large single-centre cohort study. Issue 2 (11th December 2017) - Saifuddin, Aamir; Harris, Adam
Abstract : Objective: To explore the 'real world' effectiveness of tacrolimus therapy for refractory ulcerative proctocolitis (UC). Design: Retrospective cohort study using prospectively collated clinical data. Setting: A single district general hospital in Kent, UK. Clinical decisions and regular monitoring were undertaken by a single expert in inflammatory bowel disease. Patients: All patients started on tacrolimus between January 2010 and August 2016 at Tunbridge Wells Hospital. Interventions: Following failure of conventional medication, tacrolimus was commenced at 0.5 mg/kg twice daily. Drug trough levels of 5–20 ng/mL were targeted. Other immunomodulation was stopped and steroids were weaned over 4–6 weeks. Main outcome measures: Treatment duration was measured for each patient. If the drug was stopped, the rationale, including specific side effects, was recorded. The patient's subsequent management plan was noted. Results: Thirty-five patients were started on tacrolimus (range: 18–85, median: 36 years). Disease extent included proctitis to pancolitis. Twenty-five patients derived no benefit. Four patients responded, but drug side effects necessitated withdrawal. Eighteen of these 29 patients (62%) underwent surgery. One patient, who had previously responded, stopped the drug after becoming pregnant (healthy subsequent birth). Therefore, 5 of 35 patients (14%) remain on tacrolimus with sustained clinical response, ranging from 6 to 76 (median: 32) months of treatment. Treatment was most effective for proctosigmoiditis. There were no other demographic or biological markers for success. Conclusions: In line with UK and European guidelines, tacrolimus can be beneficial for refractory UC. With appropriate monitoring, it appears treatment can be continued safely long term.